Etude de l’activité anti-inflammatoire de Centaurea s.p « étude histologique chez la souris » - YANOUI, Kanza; TEHAMI, Sara (My University, 2017)
Cntaurea s.p is a plant which is known by its therapeutic effect. It’sused in traditional medicine to treatthe skin burns. Inflammatory diseases is one of these pathologies which can be preserved by this plant. The extract of Centaurea s.p was tested for its anti-inflammatory effect. This activity was assessed in vivo by the test of the edemaled by the carragenine. A test of toxicity of the aqueous extract in the doses 150 and 300mg/kg BW, respectively accomplished in oral administration. The results show that in these doses, the extract has no toxic effect. On the other hand, the treatment of the inflamation was given one hour before causing the acute inflammation by the injection of carragenine 0,1%. So, the teste of the extract in the doses 150 and 300mg/kg BW showed a asignificant anti-inflammatory activity (P<0,001) compared with the control mice. The inhibition percent of the edema reach 80% for the dose 150mg/kg BW against 50% of inhibition for Diclofenac. The histological study of cutstreated by Diclofenac and the aqueous extract of Centaurea s.p (150 and 300mg/kg BW) confirm that the extract of the plant has an anti-inflammatory activity. Besides, in the dose 150 and 300mg/kg BW the inflammatory infiltrate disappears almost completely. The presence of anti-inflammatory activity in the doses of aqueous extract of centaurea s.p can be applied in the therapeutic field.
Keywords: Centaurea s.p; Activité anti-inflammatoire; Histologie; anti-inflammatoryactivity; Histology.